ANALISIS RESILIENSI USAHA, MIKRO, KECIL, DAN MENENGAH (UMKM) DI KOTA SEMARANG - Andini Viyonita; Ida Hayu Dwimawanti (Journal of Management and Public Policy, 2026)
This study aims to analyze the resilience of Micro, Small, and Medium Enterprises (MSMEs) in Semarang City in facing challenges from the onset of the COVID-19 pandemic to the present, as well as to identify the factors supporting this resilience. The study employs a descriptive qualitative method using a case study approach. Data were collected through interviews and documentation from six MSME operators in the handicrafts, food, beauty and fashion, and food processing sectors, as well as one informant from the Semarang City Cooperative and SME Agency. Data analysis was conducted using the Miles and Huberman model through data reduction, data presentation, and the drawing of conclusions and verification with the assistance of ATLAS.ti. The research results indicate that the resilience of MSMEs in Semarang City is relatively good, although it is not yet evenly distributed across all dimensions. Business owners generally demonstrate the ability to respond to changes by adjusting services and marketing strategies, monitoring market needs, understanding business risks, and building adaptive capacity. However, vulnerability management remains a relatively weaker area, particularly regarding the stability of raw materials, inventory, capital, and business contingency preparedness. Factors supporting resilience include information management, stakeholder networks and collaboration, preparedness and planning, alternative routes and redundancy, as well as vulnerability management. Therefore, efforts to strengthen resilience should focus on improving vulnerability management, expanding access to information, and ensuring government programs are communicated and documented in a more equitable, targeted, and needs-based manner for MSMEs in the future.